Energy efficient SBSs sleep mode analysis for successive user association and resource scheduling algorithms in two‐tier heterogeneous network. Issue 9 (1st June 2019) - Peng, Xuefei; Li, Jiandong; Zhang, Hao
Abstract : This study analyses and compares the downlink energy efficiency (EE) of user association and resource scheduling algorithms considering sleep mode of small cell base stations (SBSs) in two‐tier heterogeneous cellular networks. Owing to the NP‐hardness of joint user association and resource scheduling algorithms, the authors successively perform user association and resource scheduling algorithms. Firstly, in the user association algorithms, sleep mode for the SBSs without associated users is considered to improve EE, where they associate users with the macrocell base station (MBS) or SBSs according to three signal strength strategies, namely, unbiased user association, biased user association and signal to interference plus noise ratio‐based user association. Then, in the resource scheduling algorithms, they schedule the MBS and SBSs resource blocks to users based on three scheduling criteria, i.e. maximum received signal strength, round robin and proportional fairness, respectively. Fairness among users is also analysed. In the simulation, numerical results for different successive user association and resource scheduling algorithms are compared. The optimum algorithms are found in the different network environments. These results are significant for the heterogeneous network operation to get high EE.